The Effect of Tax Socialization on Taxpayer Compliance in Bandung (The Indonesian Journal of Business Administration, 2020)
Lack of socialization of taxation can lead to ignorance of tax knowledge and consequentlynon-compliance with regulations. Lack of adequate tax facilities and infrastructure also results in alack of motivation to report taxes. The higher the level of taxpayer compliance, the higher the level oftax success. Thus the tax target can be achieved. This study aims to determine the expectations oftaxpayers on tax socialization and to analyze the effect of tax socialization on taxpayer compliance inthe city of Bandung. The research method used is quantitative, with descriptive and causal researchtypes. Sampling with the simple random sampling method with a sample of 400 people. Taxpayersprefer direct socialization. The material that taxpayers expect is the reporting of annual personal taxreturns, held in the first quarter, namely January - March, with a duration of 30-45 minutes, and usingpersonal devices. Socialization using billboards or street advertisements is also adequate. The resultsof the descriptive analysis shows that the tax socialization variable is in a good category. Likewise, thetaxpayer compliance variable is included in the good category. The results of regression analysis andthe coefficient of determination show that tax socialization has a positive effect on taxpayercompliance and it also add on the significance to taxpayer compliance in Bandung.Keywords: Tax, Tax Socialization, Taxpayer Compliance